Kajian Hukum Perdata Terhadap Penggunaan Perjanjian Digital Dalam Kegiatan Bisnis (Studi Kasus Di Idola Bencoolen) - Rohan Manatanael Panjaitan; Uswatun Hasanah; Marlinah Marlinah (Journal of Innovative and Creativity, 2025)
The purpose of this study is to determine the use of digital contracts in business in Idol, Bengkulu. This study uses empirical legal methods to discuss the problem of electronic contracts. Its relevance is verified using the Civil Code, qualitative interviews, and observations. The results of the study indicate that several businesses in Bengkulu use electronic contracts for their digital business activities. The parties who make the contract are free to determine the form of the contract made, but they are bound by the provisions of the main contract and are regulated by law, namely by agreement of the parties who make the contract. Electronic contracts are valid and legally binding.